Studi Komparatif Kebijakan Amerika Serikat dalam Merespon Kebangkitan Tiongkok pada Masa Pemerintahan Barack Obama dan Donald Trump - Wardhana, Danar Hafidz Adi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study discusses a comparative analysis of the United States' policy in responding to the rise of China during the administrations of Barack Obama and Donald Trump. The focus of this research is to analyze the differences in foreign policy approaches applied by both presidents in addressing China's economic, political, and military influence on the global stage. The research method used is qualitative analysis with a descriptive-comparative approach to examine the diplomacy, trade, and security strategies adopted by both administrations. The findings show that the Barack Obama administration emphasized a multilateral approach through cooperation with allied countries and initiatives such as the Trans-Pacific Partnership (TPP) to counter China's economic expansion. In contrast, the Donald Trump administration implemented a more confrontational policy with trade war strategies, high import tariffs, and unilateral policies aimed at economically pressuring China. The conclusion of this study shows that although both administrations had the same objective of limiting China's dominance, their approaches differed significantly. The Obama administration prioritized diplomacy and alliances, while the Trump administration focused on economic pressure and protectionist policies. This study is expected to provide a deeper understanding of the dynamics in the United States-China relations and the implications of both countries' foreign policies in the future.